Association of household income and adverse outcomes in patients with atrial fibrillation. Issue 21 (6th March 2020) - LaRosa, Anna Rose; Claxton, J'Neka; O'Neal, Wesley T; Lutsey, Pamela L; Chen, Lin Y; Bengtson, Lindsay; Chamberlain, Alanna M; Alonso, Alvaro; Magnani, Jared W
Abstract : Background: Social determinants of health are relevant to cardiovascular outcomes but have had limited examination in atrial fibrillation (AF). Objectives: The purpose of this study was to examine the association of annual household income and cardiovascular outcomes in individuals with AF. Methods: We analysed administrative claims for individuals with AF from 2009 to 2015 captured by a health claims database. We categorised estimates of annual household income as <$40 000; $40–$59 999; $60–$74 999; $75–$99 999; and ≥$100 000. Covariates included demographics, education, cardiovascular disease risk factors, comorbid conditions and anticoagulation. We examined event rates by income category and in multivariable-adjusted models in reference to the highest income category (≥$100 000). Results: Our analysis included 336 736 individuals (age 72.7±11.9 years; 44.5% women; 82.6% white, 8.4% black, 7.0% Hispanic and 2.1% Asian) with AF followed for median (25th and 75th percentile) of 1.5 (95% CI 0.6 to 3.0) years. We observed an inverse association between income and heart failure and myocardial infarction (MI) with evidence of progressive risk across decreased income categories. Individuals with household income <$40 000 had the greatest risk for heart failure (HR 1.17; 95% CI 1.05 to 1.30) and MI (HR 1.18; 95% CI 0.98 to 1.41) compared with those with income ≥$100 000. Conclusions: We identified an association between lower household income and adverse outcomes in a large cohort of individuals with AF. Our findings support consideration of income in the evaluation of cardiovascular risk in individuals with AF.